Pregnant Women's Experiences of the Conditions Affecting Marital Well-Being in High-Risk Pregnancy: A Qualitative Study - Kobra Mirzakhani; Talaat Khadivzadeh; Farhad Faridhosseini; Abbas Ebadi (Shiraz University of Medical Sciences, 2020)
Background: High-risk pregnancy is associated with many problems which can affect marital wellbeing as well as maternal and fetal health. Yet, there is limited information about the conditions which affect marital well-being in high-risk pregnancy. This study aimed to explore the pregnant women's experiences of the conditions affecting marital well-being in high-risk pregnancy Methods: This qualitative study was conducted from October 2018 to December 2019. Participants were 24 women with high-risk pregnancy who were purposively selected from three public and two private hospitals as well as a primary healthcare center in Mashhad, Iran. Face-to-face semi-structured interviews were conducted for data collection. Data were analyzed concurrently with data collection through Graneheim and Lundman's content analysis (2004). The MAXQDA program (v. 10) was used for data management. Results: Conditions affecting marital well-being in high-risk pregnancy were categorized into eleven subcategories and three main categories, namely emotional spousal intimacy in the midst of danger, husband's commitment to manage the difficult conditions of pregnancy and sexual relationship during high-risk pregnancy. Conclusion: Several conditions can affect marital well-being in high-risk pregnancy. Healthcare providers can develop and use strategies for the effective management of these conditions, thereby improving marital well-being among women with high-risk pregnancy.